Laboratory determinants of repeated-sprint and sport-specific-technique ability in world-class ice sledge hockey players - Baumgart, J. K.; Sandbakk, O. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To investigate on-ice repeated-sprint and sports-specific-technique abilities and the relationships to aerobic and anaerobic off-ice capacities in world-class ice sledge hockey players. Methods: Twelve Norwegian national team players performed 8 repeated maximal 30-m sprints and a sports-specific-technique test while upper-body poling on ice, followed by 4 maximal upper-body strength tests and 8-s peak power and 3-min peak aerobic-capacity (VO2peak) tests while ergometer poling. Results: The fastest 30-m sprint time was 6.5 ± 0.4 s, the fastest initial 10-m split-time 2.9 ± 0.2 s, and the corresponding power output 212 ± 37 W. Average 30-m time during the 8 repeated sprints was 6.7 ± 0.4 s, and the sprint-time decrement was 4.3% ± 1.8%. Time to execute the sport-specific-technique test was 25.6 ± 2.7 s. Averaged 1-repetition-maximum strength of the 4 exercises correlated with the fastest 30-m sprint time (r = -.77), the fastest initial 10-m split time (r = -.72), the corresponding power output (r = .67), and the average 30-m sprint time (r = -.84) (all P < .05). Peak power of the 8-s ergometer sprint test correlated with the highest initial 10-m power (r = .83, P < .01) and the average 30-m sprint time (r = -.68, P < .05). Average 3-min ergometer power (r = -.86, P < .01) and VO2peak (r = -.67, P < .05) correlated with the sprint-time decrement. All off-ice variables except VO2peak correlated with technique-test time (r = -.58 to .73, all P < .05). Conclusion: Maximal strength and power are associated with the ability to sprint fast and rapid execution of a technically complex test, whereas mode-specific endurance capacity is particularly important for maintenance of sprint ability in ice sledge hockey.